Assessment of microbiological quality of ready-to-eat foods in institutions providing mass feeding - Dağ, Ayhan (Progress in Nutrition, 2020)
Objective: This study was designed to evaluate microbiological quality of ready-to-eat foods in institutional mass feeding and to determine their risk for food poisoning. In the study, 275 ready-to-serve food samples were evaluated in institutional feeding. The food groupings in the Turkish Food Codex Regulation Supplementary Document I and parameters established in food safety criteria in Supplementary Document I and III were adopted. The samples were analyzed for parameters about coagulase-positive Staphylococci (TS EN ISO 6888-1/A1), B. cereus (TS EN ISO 7932), E. coli (TS ISO 16649-2), Staphylococcal enterotoxins (AOAC OMA) 2007.06 - VIDAS SET 2), Salmonella spp. (TS EN ISO 6579-1), L. monocytogenes (TS EN ISO 11290-1) and mold - yeast (TS ISO 21527-1/2) by reference methods. Of the samples analyzed, 250 samples (90.9%) were found appropriate for consumption while 25 samples (9.1%) as inappropriate according to Microbiological Criteria Regulation. It was concluded that meats served warm carry risk for L. monocytogenes, B. cereus and E. coli parameters while salads-appetizers served cool carry risk for L. monocytogenes and Salmonella spp. and deserts, particularly cream cakes, carry risk for E. coli and mold - yeast parameters.